Building in Existing Fabric : Refurbishment, Extensions, New Design - Schittich, Christian (in DETAIL, 2012)
This publication examines a wide range of unconventional concepts for reusing existing buildings, highlighting successful and innovative solutions, from the reuse of a gothic monastery or the former industrial buildings of Fiat Lingotto to the renovation of structures made of pre-cast concrete panels.